Dragonheart - McCaffrey, Todd 1956- (New York Del Rey Ballantine Books, 2009)
aWhen young Fiona is asked to take on the role of Weyrwoman, she soon discovers the challenges of her new position, from unexpected perils to the possibility of losing her own dragon to the sickness that has claimed others
Keywords: Dragons -- Fiction; Life on other planets -- Fiction; Pern (Imaginary place) -- Fiction; Space colonies -- Fiction